Existence of positive solutions for a coupled system of nonlinear boundary value problems of fractional order with integral boundary conditions (2017)
In this work, we discuss the existence of positive solutions for a coupled system of nonlinear boundary value problems of fractional order with integral boundary conditions. The existence result is obtained by means of Krasnosel’skii fixed-point theorem in a cone.